The Predicted Financial Distress in Indonesian Startups Before And During The Massive Layoffs Phenomenon Using Springate Model - Arvianty, Atha Jauza; Andayani, Wuryan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Indonesia, ranked fifth globally for the number of startups, has experienced rapid growth in its startup ecosystem. However, this expansion faced significant challenges in 2022, marked by widespread layoffs, company closures, and bankruptcies. This research analyzes the financial distress of startup companies listed on the Indonesia Stock Exchange (IDX) during the mass layoffs of 2021 and 2022, using the Springate model. Employing a quantitative approach with purposive sampling, 15 startup companies were selected for analysis. Secondary data from financial reports obtained through the IDX was examined using the Springate model, along with descriptive statistics, normality tests, and the Wilcoxon Signed-Rank Test. The results indicate no significant difference in the financial distress levels of these companies before and during the mass layoffs. The findings suggest that financial distress, as measured by the Springate model, is not a determining factor in the occurrence of mass layoffs. This highlights the need to explore other factors contributing to such workforce reduction.